Strategic Supply Chain Participation and SME Demand Expectations under Environmental Turbulence: Evidence from Italian SMEs - Garbelli, Maria (European Scientific Journal, ESJ, 2026)
Small and medium-sized enterprises (SMEs) represent a cornerstone of the Italian industrial system, particularly within strategic supply chains (SSC) that are increasingly regarded as critical to resilience and competitiveness. However, existing literature suggests that the benefits of supply chain integration may not be unequivocal, especially under conditions of heightened market turbulence. This study investigates whether participation in strategic supply chains influences SMEs’ short-term demand expectations in uncertain economic environments. Adopting a contingency-based perspective, the analysis is based on a structured survey of 183 SMEs operating in Lombardy, one of Europe’s most industrialised regions. The empirical strategy combines descriptive analysis, non-parametric testing (Mann–Whitney U), and ordered logistic regression to assess differences in demand expectations between SSC-affiliated and non-affiliated firms. The results show that SMEs embedded in strategic supply chains report significantly more negative short-term demand expectations compared to independent firms, despite exhibiting stronger structural characteristics. This finding challenges the conventional assumption that supply chain participation stabilises firm outlook during periods of turbulence and suggests that embeddedness may increase exposure to systemic risks. The study contributes to the literature by providing empirical evidence supporting a contingency-based interpretation of supply chain participation. It also offers managerial and policy implications by highlighting the importance of adaptive and flexible supply chain governance in turbulent environments.